Efficiency Enhancement of GaAs Thermophotovoltaic Cells System using Integrated TiO2/SiO2 1D Photonic Crystal Distributed Bragg Reflectors - Yadav, Praveen Kumar; Chahal, Rishi Pal; Singh, Aman Pal (Photonics Letters of Poland, 2025)
Thermophotovoltaic (TPV) systems rely on spectrally selective reflectors to enhance conversion efficiency by maximizing photon flux above the photovoltaic bandgap while suppressing sub-bandgaps thermal losses. This work presents a numerical analysis and simulation of SiO2/TiO2 multilayer photonic crystal Distributed Bragg’s Reflectors (DBRs) tailored to the GaAs bandgap (≈ 872 nm). Transfer Matrix Method (TMM) was applied to investigate optical properties of the structure with layer’s thickness, number of periods, and refractive index contrast. Investigation demonstrate that optimized multilayer design exhibit narrowband reflection peaks centered around 800 – 1000 nm (≈ 200 nm), closely matched to the GaAs photovoltaic cutoff wavelength, with reflectivity exceeding 0.99. Beyond 1000 nm, reflectivity is strongly suppressed, minimizing energy reflections associated with unusable infrared photons. The stability analysis with angular and polarization suggests the robust performance over a wide range of angle of incidences, which are critical requirement for practical and efficient TPV operations. The numerical and simulation findings highlight the potential of SiO2/TiO2 1D photonic crystal thermally stable, tunable selective reflectors, offering a viable pathway for efficiency enhancement in GaAs-based TPV systems. Full Text: PDF References Z. Omair, S. Hooten, V. Menon, P. Oduor, K-K Choi, A.K. Dutta, "Broadband mirrors for thermophotovoltaics", Opt. Express 32, 11000 (2024). CrossRef LaPotin, A., Schulte, K.L., Steiner, M.A. et al. "Thermophotovoltaic efficiency of 40%", Nature 604, 287 (2022). CrossRef T. Inoue, T. Suzuki, K. Ikeda, T. Asano, S. Noda, "Near-field thermophotovoltaic devices with surrounding non-contact reflectors for efficient photon recycling", Opt. Express 29, 11133 (2021). CrossRef C. Juseok, H. Koohee, K. Jung, "Enhanced near infrared reflectance of TiO2/SiO2/TiO2 multilayer structure using a base-catalyzed SiO2 film", Thin Solid Films. 569, 100 (2014). CrossRef A. Kotbi, W.E. Hakim, P. Barroy, et al. "Selecting the state of shape memory alloys by optical filtering", Opt Quant Electron 57, 534 (2025). CrossRef J. Xi, E. Schubert, D. Ye, T. Lu, S.H. Lin, J. Juneja, "Very low-refractive-index optical thin films consisting of an array of SiO2 nanorods", Optics Lett. 31, 601 (2006). CrossRef G. Christidis, O. Fabrichnaya, S. Koepfli, E. Poloni,J. Winiger,Y. Fedoryshyn, A. Gusarov, M. Ilatovskaya, I. Saenko, G. Savinykh, V. Shklover, J. Leuthold, "Photonic response and temperature evolution of SiO2/TiO2 multilayers". J. Mater. Sci. 56 (2021). CrossRef D. Kim, K.M. Kim, H. Han, et al. "Ti/TiO2/SiO2 multilayer thin films with enhanced spectral selectivity for optical narrow bandpass filters". Sci Rep 12, 32 (2022). CrossRef G. Hwang, G. Bak, Y. Kim, S.H. Jung, H. Na, Y.J. Jung, "Highly Reflective Organic/Inorganic Hybrid 1D Photonic Crystals Based on Silane-Functionalized TiO2 Nanoparticles for Colorimetric Humidity and Alcohol Vapor Sensing", ACS Omega 10(32), 36582 (2025). CrossRef S. Chen, T. Zhu, F. Juan, Y. Zhu, J. Xu, K. Chen, "High-temperature stable and efficient broadband solar absorber based on Si/metal plasmonic structures", Solar Energy. 276. 112664 (2024). CrossRef F.K. Mbakop, R.Z. Falama, F. Wu, A. Ayang, S.N. Essiane, L. Leontie, N. Djongyang, F. Iacomi, "Angular dependence of photonic band gap and omni-directional reflection in one-dimensional photonic crystal applied to a thermophotovoltaic device", Results in Optics, 14, 100594 (2024). CrossRef Z. Zhou, O. Yehia, P. Bermel, "Integrated photonic crystal selective emitter for thermophotovoltaics", J. Nano photonics. 10(1), 016014 (2016). CrossRef M.B. Panish, H.C. Casey, "Temperature Dependence of the Energy Gap in GaAs and GaP", J. Appl. Phys. 40(1), 163 (1969). CrossRef M. Suemitsu, T. Asano, T. Inoue, S. Noda, "High-Efficiency Thermophotovoltaic System That Employs an Emitter Based on a Silicon Rod-Type Photonic Crystal", ACS Photonics 7(1), 80 (2020). CrossRef L. Farah, A.B. Hadjira, A. Mehadji, "A Novel 1.31 um Narrow-band TE-Mode filter Design based on PBG Shift in 2D Photonic Crystal Slab", Photonics Lett. Pol., 8(3), 82 (2016). CrossRef N.L. Kazanskiy, M.A. Butt, "One-dimensional photonic crystal waveguide based on SOI platform for transverse magnetic polarization-maintaining devices", Photonics Lett. Pol.,12(3), 85 (2020). CrossRef O.H. Jaworska, S. Ertman, "Photonic Bandgaps In Selectively Filled Photonic Crystal Fibers", Photonics Lett. Pol.,9(3), 79 (2017). CrossRef D.M. Mead, "Wave Propagation In Continuous Periodic Structures: Research Contributions From Southampton, 1964-1995", Journal Of Sound And Vibration, 190(3),495 (1996). CrossRef